2000
DOI: 10.1038/sj.bmt.1702626
|View full text |Cite
|
Sign up to set email alerts
|

Response to thalidomide therapy in refractory chronic graft-versus-host disease

Abstract: Summary:Chronic graft-versus-host disease (GVHD) refractory to standard immunosuppressive therapy remains a major cause of morbidity and mortality after allogeneic bone marrow transplantation (BMT). Thalidomide may be effective in some patients with high-risk or refractory chronic GVHD. We report a single-institution study of thalidomide in 37 BMT patients with extensive chronic GVHD refractory to standard immunosuppressive therapy. Acute GVHD occurred in 34 (91%) of patients and evolved progressively into chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 17 publications
3
32
0
2
Order By: Relevance
“…50 Browne e cols 51 estudaram seu uso em 37 pacientes e observaram 38% de resposta global (78% nas articulações e 46% na pele) e sobrevida de 41% em dois anos. Estudo pré-vio 52 com amostra maior (n = 80) reportou 20% de resposta com alta taxa (36%) de efeitos adversos e suspensão da droga (CIa).…”
Section: Tratamento De Resgateunclassified
“…50 Browne e cols 51 estudaram seu uso em 37 pacientes e observaram 38% de resposta global (78% nas articulações e 46% na pele) e sobrevida de 41% em dois anos. Estudo pré-vio 52 com amostra maior (n = 80) reportou 20% de resposta com alta taxa (36%) de efeitos adversos e suspensão da droga (CIa).…”
Section: Tratamento De Resgateunclassified
“…Despite one case report of BO responding to thalidomide, 43 a recent study has shown no benefit in pulmonary chronic GVHD. 44 Intravenous immunoglobulin has not been shown to prevent the development of BO. 45 Cyclosporine may prevent the development of BO.…”
Section: Treatmentmentioning
confidence: 99%
“…Six complete responses and four partial responses were reported. Browne et al 65 treated 37 subjects with advanced cGVHD with thalidomide, 200-800 mg/day. In all, 1 subject had a complete and 13, partial responses.…”
Section: Imid-class Drugsmentioning
confidence: 99%